2021
DOI: 10.3389/fgene.2021.624581
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in Prader-Willi Syndrome

Abstract: Prader-Willi Syndrome (PWS) is a rare neurodevelopmental disorder that affects approximately 1 in 20,000 individuals worldwide. Symptom progression in PWS is classically characterized by two nutritional stages. Stage 1 is hypotonia characterized by poor muscle tone that leads to poor feeding behavior causing failure to thrive in early neonatal life. Stage 2 is followed by the development of extreme hyperphagia, also known as insatiable eating and fixation on food that often leads to obesity in early childhood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 145 publications
0
8
0
Order By: Relevance
“…This mechanism establishes the original silencing of maternal chromosome. Recently, the existence of separate somatic imprints in this silencing activity has been uncovered [70,71]. The epigenetic DNA-methylation that is mediated by DNA methyltransferase enzyme has been considered as a therapeutic target for possible management of PWS.…”
Section: Epigenetic Causementioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism establishes the original silencing of maternal chromosome. Recently, the existence of separate somatic imprints in this silencing activity has been uncovered [70,71]. The epigenetic DNA-methylation that is mediated by DNA methyltransferase enzyme has been considered as a therapeutic target for possible management of PWS.…”
Section: Epigenetic Causementioning
confidence: 99%
“…The first proof of principle of this approach was obtained when it was shown that a DNA methyltransferase inhibitor, '5-azadeoxycytidine' was able to demethylate the PWS-IC leading to activation of the maternal genes. Therefore, activation of the normally silent such maternal gene inhibitory compound may offer a potential therapeutic intervention and treatment for PWS patients [70,71]. Recently, a protein named 'ZNF-274' (Zinc Finger Protein 274) that contains five Zinc-finger domains has been identified [72], which plays important role in the suppression of maternal chromosome-15q11-q13 allele.…”
Section: Epigenetic Causementioning
confidence: 99%
“…On the paternal allele of imprinted human PWS/AS locus, the unmethylated PWS-ICR is the region upstream to a protein-coding gene SNRPN and a lncRNA SNHG14 (small nucleolar RNA host gene 14) ( Sutcliffe et al, 1994 ; Buiting et al, 1995 ; Rougeulle et al, 1997 ; Runte et al, 2001 ; Vitali et al, 2010 ; Chamberlain, 2013 ; Stanurova et al, 2018 ; Figure 4A ). The neuron-specific non-coding transcript SNHG14 is processed to give rise to a series of non-coding RNA products, such as repeated C/D box small nucleolar RNAs (snoRNAs) and lncRNAs including 116HG , 115HG , and the antisense transcript to UBE3A ( Mendiola and LaSalle, 2021 ; Figure 4A ). The most studied RNA product from the host transcript SNHG14 is SNORD116 snoRNA, embedded within intronic regions of SNORD116 gene locus ( Cavaillé et al, 2000 ; de los Santos et al, 2000 ; Stanurova et al, 2018 ; Mendiola and LaSalle, 2021 ).…”
Section: The Role Of Imprinted Long Non-coding Rnas In Human Imprinting Disorders and Cancermentioning
confidence: 99%
“…The neuron-specific non-coding transcript SNHG14 is processed to give rise to a series of non-coding RNA products, such as repeated C/D box small nucleolar RNAs (snoRNAs) and lncRNAs including 116HG , 115HG , and the antisense transcript to UBE3A ( Mendiola and LaSalle, 2021 ; Figure 4A ). The most studied RNA product from the host transcript SNHG14 is SNORD116 snoRNA, embedded within intronic regions of SNORD116 gene locus ( Cavaillé et al, 2000 ; de los Santos et al, 2000 ; Stanurova et al, 2018 ; Mendiola and LaSalle, 2021 ). SNORD116 snoRNA present in ribonucleoprotein complexes (snoRNPs) and may participate in splicing, ribosomal RNA maturation, RNA modifications, and regulation of prohormone processing-related gene expression ( Bazeley et al, 2008 ; Burnett et al, 2017 ).…”
Section: The Role Of Imprinted Long Non-coding Rnas In Human Imprinting Disorders and Cancermentioning
confidence: 99%
See 1 more Smart Citation